ANALYSIS OF MATHEMATICAL WRITING ERRORS RELATED TO THE ANGLE OF TRIGONOMETRI FUNCTIONS - Budi Mulyono; Hapizah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Mathematical writing errors are often made by students, especially when writing mathematical expressions on the angle of trigonometric functions. One of the causes of this error is that students do not pay close attention to the difference between radians and degrees when writing questions or writing answers. These mathematical writing errors were made mainly by students who were oriented towards the result of the answer to a question, without paying attention to good and correct writing rules. One form of writing errors in mathematical expressions of trigonometric functions is writing y = sin (x + 45), which is considered the same as writing y = sin (x + 45o). If they are asked to compare the graphical form of the function of the two mathematical expressions in the same image, the writing error will be recognized and seen. Counterexamples and technology in learning mathematics can help students understand and correct errors in writing mathematical expressions of trigonometric functions.